Length of hospital stay and mortality associated with burns from assault: a retrospective study with inverse probability weighting analysis. Issue 1 (1st April 2020) - Yamamoto, Ryo; Toyosaki, Mitsunobu; Kurihara, Tomohiro; Sasaki, Junichi
Abstract: Background: Burns resulting from assaults account for considerable morbidity and mortality among patients with burn injuries around the world. However, it is still unclear whether unfavorable clinical outcomes are associated primarily with the severity of the injuries. To elucidate the direct relationship between burns resulting from assaults and mortality and/or length of hospital stays, we performed this study with the hypothesis that burns from assault would be independently associated with fewer hospital-free days than would burns from other causes, regardless of the severity of burn injuries. Methods: We conducted a retrospective cohort study, using a city-wide burn registry (1996–2017) accounting for 14 burn centers in Tokyo, Japan. Patients who arrived within 24 hours after injury were included, and those with self-inflicted burn injuries were excluded. Patients were divided into two groups according to mechanism of burns (assault vs. accident), and the number of hospital-free days until day 30 after injury (a composite of in-hospital death and hospital length of stay) was compared between the groups. To estimate the probability that an injury would be classified as an assault, we calculated propensity scores, using multivariate logistic regression analyses adjusted for known outcome predictors. We also performed an inverse probability weighting (IPW) analysis to compare adjusted numbers of hospital-free days. Results: Of 7419 patients in the registry with burn injuries during the study period, 5119 patients were included in this study. Of these, 113 (2.2%) were injured as a result of assault; they had significantly fewer hospital-free days than did those with burns caused by accident (18 [27] vs. 24 [20] days; coefficient = $-$ 3.4 [$-$ 5.5 to $-$ 1.3] days; p  = 0.001). IPW analyses similarly revealed the independent association between assault burn injury and fewer hospital-free days (adjusted coefficient = $-$ 0.6 [$-$ 1.0 to $-$ 0.1] days; p  = 0.009). Conclusions: Burn from assault was independently associated with fewer hospital-free days, regardless of the severity of burn injuries. The pathophysiological mechanism underlying the relationship should be further studied in a prospective observational study.